Unveiling the Diversity: A Novel Species of Dicephalospora (Helotiaceae, Helotiales) Discovered in China - Luo, L.; Wei, D.p.; Zhao, Q.; Thilini Chethana, K.w. (Phytotaxa, 2024)
Dicephalospora is a discomycete belonging to the fungus family Helotiaceae (Helotiales). In the present study, a new species of Dicephalospora is identified based on morphological characteristics and phylogenetic analyses of combined ITS and LSU sequences. Dicephalospora xishuangbannanensis sp. nov. is characterized by yellow-orange, stipitate apothecia, eight-spored, unitunicate, 106–134 × 8.2–12.2 µm, cylindrical to clavate, J- asci, and fusiform, 19–27 × 4–6 µm, guttulate ascospores with a gelatinous sheath at both ends. An updated key to the known species of Dicephalospora is provided.